'Wide‐awake drunkenness'? Investigating the association between alcohol intoxication and stimulant use in the night‐time economy. (23rd October 2014) - Pennay, Amy; Miller, Peter; Busija, Lucy; Jenkinson, Rebecca; Droste, Nicolas; Quinn, Brendan; Jones, Sandra C.; Lubman, Dan I.
Abstract Aims We tested whether patrons of the night‐time economy who had co‐consumed energy drinks or illicit stimulants with alcohol had higher blood alcohol concentration (BAC) levels than patrons who had consumed only alcohol. Design Street intercept surveys (n = 4227) were undertaken between 9 p.m. and 5 a.m. over a period of 7 months. Setting Interviews were undertaken with patrons walking through entertainment precincts, queuing to enter venues or exiting venues in five Australian cities. Participants The response rate was 92.1%; more than half the study sample was male (60.2%) and the median age was 23 years (range 18–72). Measurements Data were collected on demographics, length of drinking session, venue types visited, types and quantity of alcohol consumed and other substance use. A BAC reading was recorded and a subsample of participants was tested for other drug use. Findings Compared with the total sample (0.068%), illicit stimulant consumers (0.080%; P = 0.004) and energy drink consumers (0.074%; P < 0.001) had a significantly higher median BAC reading, and were more likely to engage in pre‐drinking (65.6, 82.1 and 77.6%, respectively, P < 0.001) and longer drinking sessions (4, 5 and 4.5 hours, respectively, P < 0.001). However, stimulant use was not associated independently with higher BAC in the final multivariable model (illicit stimulants P = 0.198; energy drinks P = 0.112). Interaction analyses showed that stimulant users had a higher BAC in the initial stages of the drinking session, but not after 4–6 hours. Conclusions While stimulant use does not predict BAC in and of itself, stimulants users are more likely to engage in prolonged sessions of heavy alcohol consumption and a range of risk‐taking behaviours on a night out, which may explain higher levels of BAC among stimulants users, at least in the initial stages of the drinking session.